Critical review of the addition of tumor treating fields (TTFields) to the existing standard of care for newly diagnosed glioblastoma patients. (March 2017) - Mehta, M.; Wen, P.; Nishikawa, R.; Reardon, D.; Peters, K.
Abstract: Since 2005, the standard of care for patients with newly diagnosed glioblastoma (GBM) has consisted of maximal resection followed by radiotherapy plus daily temozolomide (TMZ), followed by maintenance TMZ. In patients selected for clinical trials, median overall survival (OS) and progression-free survival (PFS) with this regimen is 15–17 months and 6–7 months, respectively. There have been various, largely unsuccessful attempts to improve on this standard of care. With the FDA approval of the tumor-treating fields (TTFields) device, Optune, for recurrent GBM (2011), and the more recent EF-14 interim trial results and approval for newly diagnosed GBM patients, several questions have arisen. A roundtable of experts was convened at the 2015 ASCO meeting to engage in an open conversation and debate of the EF-14 results presented at that meeting and their implications for neuro-oncology practice and clinical research. In October 2015, subsequent to the roundtable discussion, TTFields received FDA approval for newly diagnosed GBM.